Capacidad de agencia de autocuidado y consumo de cigarrillo en estudiantes de pregrado de enfermería (2020)
Cigarette smoking is a public health problem and many smokers started in youth. It is important to know the relationship between cigarette smoking and the self-care agency in nursing students, due they will be promoters of healthy lifestyles. Objective: To identify the relationship between cigarette smoking and self-care agency capacity in nursing students from a public university in Colombia. Methods: cross-sectional study in nursing students from I to X semester in October 2019. A random sampling stratified by semester was used. The sample size was 247 students; they full the questionnaire for classification of cigarette consumers (C4) and the scale of appreciation of the self-care agency for Colombia; Demographic and academic variables were measured. The Chi2 and Spearman’s coefficient tests were used for statistical analysis. Results: 60% were women, the average age was 21 ±3 years, and 55% were between I to V semester. The 7%, 64% and 29% presented low, médium, and good self-care agency; 19% (46 students) reported smoking. No correlation was found between the scores of the two scales (rho -0.067; p0.296). Conclusions: no correlation was found between the score of the self-care agency scale and cigarette consumption in the nursing students. Other researches should test the same hypothesis in different university students and use other tools for evaluating cigarette smoking.